Strategi Branding Grup Musik El-Uwais melalui Pemanfaatan Media Sosial Instagram - Tanjuan Alfahiro; Eka Yusup; Tri Susanto (Jurnal Pustaka Komunikasi, 2026)
This study aims to analyze the branding strategy implemented by the El-Uwais Gambus Music Group through Instagram social media amidst the declining popularity of gambus music and increasing competition from modern music genres. This study uses a qualitative approach with the Brand Expression framework by Sisco Van Gelder to examine three main dimensions, namely brand positioning, brand identity, and brand personality. Data were obtained through in-depth interviews, observations, and documentation of the El-Uwais group owner and the social media admin who manages the group's Instagram account. The results show that El-Uwais utilizes Instagram as the main medium to display a consistent visual identity, emphasize the brand's position as a religious and modern gambus music group, and build a brand personality that is warm, communicative, and close to the audience. This strategy is supported by the use of visual content, documentation of performances, and active interaction with followers, thus helping to strengthen El-Uwais's brand image in the digital space. This research's contribution lies in explaining how the Brand Expression concept is applied in the context of digital communication to build the branding of traditional-religious music groups through Instagram. It also demonstrates that social media can be a strategic tool for expanding the reach and maintaining the existence of gambus music in the digital era.